2018
DOI: 10.1177/0009922818774339
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Unique Needs of Hospitalized Adolescents and Young Adults Referred for Psychology Consults

Abstract: Hospitalized children and adolescents/young adults (AYA) frequently have mental health concerns that may be addressed by consulting psychology. We examined demographic, medical, referral, intervention, and disposition differences between children (≤11 years) and AYA referred for a psychology consult at a pediatric hospital (N = 1091). Referred AYA were more likely to be female, have shorter lengths of stay, and repeat psychology consults. Children were more likely to be referred for anxiety or feeding; AYA wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…The high overlap between depression elevations and consults also highlights that medical providers are generally identifying and seeking appropriate services for children with depressive symptomology. This is consistent with data demonstrating that anxiety, depression, and coping/adjustment (which often includes components of anxiety and depression) are some of the most common referral concerns to pediatric psychology CL services (Kullgren et al, 2018; Piazza-Waggoner et al, 2013). It is possible that medical providers are utilizing BH CL services to address internalizing concerns more frequently than seeking additional support with symptoms management such as pain, fatigue, and mobility.…”
Section: Discussionsupporting
confidence: 90%
“…The high overlap between depression elevations and consults also highlights that medical providers are generally identifying and seeking appropriate services for children with depressive symptomology. This is consistent with data demonstrating that anxiety, depression, and coping/adjustment (which often includes components of anxiety and depression) are some of the most common referral concerns to pediatric psychology CL services (Kullgren et al, 2018; Piazza-Waggoner et al, 2013). It is possible that medical providers are utilizing BH CL services to address internalizing concerns more frequently than seeking additional support with symptoms management such as pain, fatigue, and mobility.…”
Section: Discussionsupporting
confidence: 90%
“…Hospitals may be particularly stressful environments for adolescents, who are at a vulnerable stage in their development [ 27 ]. Their health issues require different responses from the hospital system than those young children [ 28 , 29 ] or adults [ 30 ] require, because they are affected by the physical, emotional, psychological, and sociocultural stages of adolescence as they develop their identity and autonomy [ 31 ]. For example, adolescents with chronic health conditions have preferences and concepts of care that differ from those of adults [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…A general belief is that the subjective perception rather than objective characteristics of the illness/injury are of importance in predicting PTSS in children (Brosbe et al, 2011). However, there are studies that found number of operations (Faugli, Bjørnland, Emblem, Nøvik, & Diseth, 2009) and length of hospitalization (Kullgren, Sullivan, & Bravender, 2018) to be significantly associated with mental health problems of adolescents.…”
Section: Introductionmentioning
confidence: 99%